Digital Transformation of Toko Madi MSME's: Improving Business in the Digital Era - Tjandinegara, Tiffany; Fanilam Putri, Elma; Christina Chandra, Nova; Christina Chandra, Novi; Nasir, Arnold; Suardi, Citra (Fakultas Teknik dan Informatika Universitas Panca Marga, 2024)
MSMEs, which stands for Micro, Small, Medium Enterprises, have a number of problems, including the lack of use of technology in business development and obstacles in accessing market information. Digital transformation allows MSMEs to utilize technology in developing their businesses, increasing operational efficiency and better accessing market information. This research aims to utilize digital transformation in entrepreneurship in the digital era and its application in the business development of Toko Madi. This research uses a mobile application development approach to create a digital platform for MSMEs